Experimental Study of Microwave Ablation in Ex Vivo Tissues - P. Keangin (2020)
© Published under licence by IOP Publishing Ltd. Cancer is one of the leading causes of morbidity and mortality worldwide. Microwave ablation is a minimally invasive treatment procedure that uses heat from microwave energy to destroy cancer cells. The effectiveness of this technique is associated to the microwave power input and heating time of treatment during the process, as well as the type of cancer tissue. The microwave power absorbed of each cancer tissue type is different and effect on the choice of treatment conditions. This research aims to investigate the effects of tissue type and microwave power input on the temperature profile and the efficiency of cancer treatment during microwave ablation. An experiment in ex vivo different tissues of porcine during microwave ablation via microwave antenna is studied. The types of tissue studied include skin tissue, liver tissue and lung tissue. The microwave power input of 60 W, 80 W and 100 W are investigated. The heating time of 360 s is selected for the study. An infrared thermometer camera is used to measure the temperature profile of tissues. The results reveal that the temperature profile and the ablation size in the case of skin tissue are higher than the liver tissue and lung tissue, respectively. In addition, the temperature profile of all tissues increases with greater microwave power. This research provides the essential aspects for a fundamental understanding of heat transfer within porcine tissues in microwave ablation process and can be used as a guideline to improve the efficiency of cancer treatment.